Plan de mejoramiento a la planta de sacrificio Frigocafé S.A del departamento del Quindío (2015)
The initiative for the improvement plan the company FRIGOCAFFE SA It arises because of the constant complaints and grievances that are coming in often presenting itself and which do not solve them after they applied to keep track resubmission. To carry out the improvement plan became necessary work it through three stages. As a first step were taken into account surveys and interviews with clients to ascertain the problem that had been frequently presented; problem was evident in the dissatisfaction of the same, stating constant complaints and / or claims, of which the main disagreement are missing in parts of the viscera and delays in the delivery schedule. As a second part or stage a study of both internal and external factors of the company which could demonstrate the main strengths and weaknesses and the threats and opportunities that FRIGOCAFE SA has held to competition; an analysis of the success factors of competition and concluded that they must positioning and success because they have a solid organizational structure is also performed. As a third and final stage improvement plan to be implemented in the company, in order to counter any shortcomings and problems evidenced, as such strategies were developed for each area it is made; with objectives to be achieved and an action plan or carry out activities to implement both the objectives and the strategies and in turn comply with the improvement plan.